2016
DOI: 10.1002/aenm.201501590
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Stability of Li10GeP2S12 and Li7La3Zr2O12 Solid Electrolytes

Abstract: electrochemical stability window, and (3) chemical compatibility with the anode and cathode. In the past few years, major advances have been achieved in increasing the Li ionic conductivity of the solid electrolytes. The state-of-the-art solid electrolyte materials, such as Li-garnet Li 7 La 3 Zr 2 O 12 (LLZO) and Li 10 GeP 2 S 12 (LGPS) have achieved an ionic conductivity of 10 −3 to 10 −2 S cm −1 , [ 1,2 ] which are comparable to commercial organic liquid electrolytes. The high ionic conductivity in solid el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
531
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 890 publications
(584 citation statements)
references
References 47 publications
30
531
1
2
Order By: Relevance
“…Al-doped LLZTO is one of the most promising solid-state electrolytes due to its high ionic conductivity, excellent chemical stability, super mechanical strength, and desirable electrical insulation ( 29 ). LLZTO powders are well dispersed by sonication in tetrahydrofuran (THF) solvent and coated on one side of the commercial PP separator (Celgard 2400) by vacuum filtration.…”
Section: Resultsmentioning
confidence: 99%
“…Al-doped LLZTO is one of the most promising solid-state electrolytes due to its high ionic conductivity, excellent chemical stability, super mechanical strength, and desirable electrical insulation ( 29 ). LLZTO powders are well dispersed by sonication in tetrahydrofuran (THF) solvent and coated on one side of the commercial PP separator (Celgard 2400) by vacuum filtration.…”
Section: Resultsmentioning
confidence: 99%
“…3a). It is noted that Han et al 22. indicated that the wide electrochemical stability of lithium solid electrolytes is overestimated by the large lithium deposition/dissolution peaks via conventional experimental method with Li/electrolyte/inert metal semi-blocking electrode, and new experimental method is developed to evaluate the electrochemical stability of lithium solid electrolytes which uses Li/electrolyte/electrolyte-carbon/inert metal cell.…”
Section: Resultsmentioning
confidence: 99%
“…Within the projector augmented wave framework, the plane wave cutoff used for total energy calculations was set to 450 eV. The generalized gradient approach was used including the Perdew-Burke-Ernzerhof functional to describe exchange and correlation ( 30 ). The energies and residual forces were converged to 10 –6 eV and 0.02 eV Å −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%